Effect of a lower limb strength training programme on physical activity during the snowy season among community-dwelling elderly individuals. (19th May 2019) - Hasegawa, Junko; Suzuki, Hideki; Yamauchi, Taro
Abstract: Background: Promoting continued physical activity during winter in snowy-cold regions would be of benefit as a health promotion strategy among elderly individuals. Aim: To evaluate the effect of a lower limb strength training programme for elderly individuals on the daily step counts during the snowy season. Subjects and methods: Fourteen community-dwelling elderly individuals were recruited from a snowy-cold region of northern Japan. Methods: Daily step counts were measured during the snowy season in 2018 (with no exercise intervention) and 2019 (after the exercise intervention). Physical function was measured before and after the intervention, including body mass index, 30-s chair test, grip strength, normal gait speed, short-test battery for locomotive syndrome, Kihon checklist and 25-question geriatric locomotive function scale. Results: The study group included 11 women and three men (78.6 ± 5.2 years old). The exercise intervention improved physical function, with a significant increase in step count among individuals with lower baseline strength. Improved lower limb strength positively correlated with an increase in step count. Conclusion: Lower limb muscle strengthening is an effective intervention to improve physical activity during the snowy season among community-dwelling elderly.